Doing practitioner research - Fox, Mark.; Martin, Peter J.; Green, Gill, 1956- (London : SAGE, 2007)
Focusing on helping practitioners conduct research in their own organizations, this title covers in detail the range of skills and techniques necessary to make a successful start to the process of becoming an effective practitioner researcher.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Action research; Human services -- Research